Geospatial in support of EIA, SEA, and SA - Sholarin, E.; Awange, Joseph (2015)
© 2015, Springer International Publishing Switzerland. This chapter has four broad sections.The first sections explains how geospatial tools and techniques can be used in support of environmental impact assessment (EIA) process, strategic environmental assessment (SEA), and sustainability assessment (SA).The second and third provide some examples of how geospatial tools (e.g., GIS, GNSS, etc.) have been used in various sites.Sections four and five explains the concept of strategic environmental assessment (SEA) and sustainability assessment (SA), using the example of Marillana Creek Mine.The last section concludes the chapter.